Beyond Orientalism: The Case of Jenaro Pérez Villaamil. (2nd September 2016) - Hopkins, Claudia
Abstract : Nineteenth-century Spanish imagery relating to Al-Andalus offers rich material for exploring Orientalism. Focusing on the landscape painter Jenaro Pérez Villaamil (1807–1854), this article reveals the special situation of Spanish artists as both object and subject of Orientalism: their culture is orientalized by foreigners, but Spanish artists are also capable of orientalising parts of their own culture and other cultures. Existing scholarship on Pérez Villaamil has focused on his assimilation of British art and his status as one of Spain's first 'Orientalist' painters. This essay widens the perspective by foregrounding Spanish attitudes to the Islamic past. Looking beyond the orthodox label of Orientalism, what were the motivations, codes and values by which Pérez Villaamil translated Spain's Islamic past into two-dimensional images and how might they have been understood at the time? It is argued that Pérez Villaamil's work reveals a desire to resist the foreign orientalising gaze, and instruct the viewer in the 'character' of the Spanish nation. His print albums, España Artística y Monumental (which have never been analyzed in depth) and his later paintings for Isabel II are discussed as meditations on Spain's history, not necessarily based on the concept of alterity.